2012
DOI: 10.1136/oemed-2011-100307
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic investigation of an occupational illness of tobacco harvesters in southern Brazil, a worldwide leader in tobacco production

Abstract: The authors confirmed Green Tobacco Sickness in southern Brazil; the authors recommend investigation of its prevalence in tobacco-growing regions and monitoring of and education about the disease and its prevention by occupational health authorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 16 publications
5
38
2
5
Order By: Relevance
“…According to McBride et al 29 and Riquinho & Hennington 9 , this work-related disease has been documented internationally since 1970. In Brazil, epidemiological studies in São Lourenço do Sul (2011) 30 and Candelária, Rio Grande do Sul State (2009) 31 , and Arapiraca, Alagoas State (2007) 32 , showed that tobacco workers presented the same symptoms as in participants in our study during harvest season. A qualitative study by Riquinho & Hennington 6 in Rio Grande do Sul State, based on life and work histories, showed signs and symptoms of GTS in tobacco-farming families 6 , corroborating the current study, revealing people's clear perception of the potential of tobacco growing to damage their health.…”
Section: Tobacco Farming and Impacts On Health And The Environmentsupporting
confidence: 64%
“…According to McBride et al 29 and Riquinho & Hennington 9 , this work-related disease has been documented internationally since 1970. In Brazil, epidemiological studies in São Lourenço do Sul (2011) 30 and Candelária, Rio Grande do Sul State (2009) 31 , and Arapiraca, Alagoas State (2007) 32 , showed that tobacco workers presented the same symptoms as in participants in our study during harvest season. A qualitative study by Riquinho & Hennington 6 in Rio Grande do Sul State, based on life and work histories, showed signs and symptoms of GTS in tobacco-farming families 6 , corroborating the current study, revealing people's clear perception of the potential of tobacco growing to damage their health.…”
Section: Tobacco Farming and Impacts On Health And The Environmentsupporting
confidence: 64%
“…There are few studies investigating tobacco farmers' health and most of the existent studies assess GTS. 11,[16][17][18][19][20] Although agricultural work is physically demanding, we did not identify any previous studies evaluating musculoskeletal problems in tobacco farmers and found only one published paper about CLBP among rice farmers in Thailand (46.3% CLBP prevalence). Methodological differences relating to sample size and sampling procedures, as well as population and working process characteristics, may explain the difference in the prevalence of CLBP.…”
Section: Discussionmentioning
confidence: 52%
“…Dessa forma, quando os trabalhadores vão fazer a colheita dessas folhas de tabaco, suas roupas podem ficar molhadas pelo contato com a planta úmida, o que favorece a passagem da nicotina pela roupa e posteriormente o contato com a pele, podendo ocorrer sua absorção e consequentemente o aparecimento de alguns efeitos adversos. Caracteriza-se como uma intoxicação aguda, geralmente moderada, cujos principais sintomas são: dor de cabeça, náuseas, vômitos, cólicas abdominais e tonturas [1][2][3][4][5][6] . A GTS foi primeiramente descrita em literatura médica na década de 1970, nos Estados Unidos, e, posteriormente, em alguns outros países como Japão, Malásia, Itália e Índia 6,7 .…”
Section: Introductionunclassified
“…Os poucos estudos existentes mostram uma grande variabilidade na prevalência da GTS, entre 8,2 e 47,0%, durante a temporada de cultivo do tabaco 6 . No Brasil, somente recentemente uma publicação científica confirmou a ocorrência da GTS em trabalhadores de uma importante região produtora de tabaco, por meio de investigação epidemiológica realizada pelo Ministério da Saúde 3,7 . Tratou-se de um estudo de caso-controle pareado (1:1) entre pessoas envolvidas na cultura do tabaco 7 .…”
Section: Introductionunclassified
See 1 more Smart Citation